Safety of laparoscopic cholecystectomy in children using conventional instruments in a general teaching hospital by general surgeons: 14 years review - Maharjan, Shantabir; Shah, Jay Narayan; Gurung, Rajan; Shah, Shailedra; Mandal, Rajesh; Baral, Reetu (Journal of Society of Surgeons of Nepal, 2017)
Introduction: There is limited specialist facility and lack of data on gallstone and laparoscopic cholecystectomy (LC) in children locally and in the region. With one government children hospital in Nepal, specialist service is far from adequate. Utilizing existing facilities to provide service is the need. We analyzed 14 years data to look in to the safety of LC in children provided by general surgeons in a general teaching hospital with conventional LC instruments used for adults. Methods: This descriptive review included children up to 14 y of age who had cholecystectomy during 14 y period from 2002 to 2015. Data on sex, age; clinical and ultrasonography findings; risk factors for gallstone; types of surgeries; bile duct injury, would infection and in-hospital mortality were analyzed. Results: There were 61 children, 0.8% of total 7469 cholecystectomy during 14 years study period. Average age was 9 years and females were 56 (84%). Out of 58-attempted LC, 56 were completed successfully. All children had history of right upper quadrant pain. Two presented with acute calculous cholecystitis. We did not find associated risk factors for stones. There was no bile duct injury. One wound infection occurred in LC converted to open. In-hospital mortality was nil. Conclusion: Cholelithiasis and cholecystectomy in children was low at 0.8% of total. With 3.4% conversion, no bile duct injury, no hospital mortality LC was safely provided by general surgeon in a general hospital using conventional facility.